2018
DOI: 10.15567/mljekarstvo.2018.0103
|View full text |Cite
|
Sign up to set email alerts
|

Instrumental texture and sensory evaluation of fermented dairy beverages processed with reconstituted goat whey powder and a co-culture of Streptococcus thermophilus and Lactobacillus casei

Abstract: The effects of Lactobacillus casei BGP93 used as adjunct culture on the physicochemical, textural and sensory characteristics of a dairy beverage processed with goat Coalho cheese whey powder and Streptococcus thermophilus TA-40 as starter (ST-LC beverage) were investigated in comparison to a control product (ST beverage) without L. casei. No significant differences were observed between the ST and ST-LC trials concerning the acidification pattern throughout the fermentation process (P>0.05). Post-acidificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…In the development of functional foods, the study of their texture parameters and sensory acceptability also has received important attention in parallel to the investigation of their potential health benefits [ 20 , 37 , 40 , 43 ]. This is of particular concern when probiotic adjuncts are added to dairy products since their texture can be affected by these cultures [ 35 ], as verified for the desserts of the present study during storage. According to Szczesniak [ 44 ], “texture is the sensory and functional manifestation of the structural, mechanical and surface properties of foods detected through the senses of vision, hearing, touch and kinesthetic”.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…In the development of functional foods, the study of their texture parameters and sensory acceptability also has received important attention in parallel to the investigation of their potential health benefits [ 20 , 37 , 40 , 43 ]. This is of particular concern when probiotic adjuncts are added to dairy products since their texture can be affected by these cultures [ 35 ], as verified for the desserts of the present study during storage. According to Szczesniak [ 44 ], “texture is the sensory and functional manifestation of the structural, mechanical and surface properties of foods detected through the senses of vision, hearing, touch and kinesthetic”.…”
Section: Discussionsupporting
confidence: 61%
“…Other parameters such as the titratable acidity and pH are also usually used to determine the milk quality before and during the production of fermented milk products [ 34 ], which are highly dependent of the starter micro-organism used and its interaction with the adjuvant cultures [ 35 ]. Considering the effects of the lactic cultures on the titratable acidity of products, the results for desserts of this study were consistent with the values typically observed for other fermented dairy products marketed in Brazil, such as fermented milks (0.6–2.0 g of lactic acid 100 g −1 ) and yoghurts (0.6–1.5 g of lactic acid 100 g −1 ), as recommended by the Brazilian regulatory standards [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effect of storage conditions on the prebiotic activity score of the synbiotic KMB powder a The reconstituted drink from synbiotic KMB powder stored at 25 °C showed an OA of 5.03 on the last day of the shelf life. Marcela de Souza Pereira et al (2018)49 conducted a similar study on sensory evaluation of dairy beverages made using reconstituted goat whey powder and fermented using Streptococcus thermophilus and Lactobacillus casei. The authors reported that the sensory acceptability did not differ signicantly even aer 7, 14, and 21 days of storage (P > 0.05).…”
mentioning
confidence: 99%